PERILAKU PENGGUNA DALAM MENGELOLA TAB, EKSTENSI, DAN BOOKMARK DI GOOGLE CHROME BAGI SISWA SMPN 1 BANYUPUTIH SITUBONDO - Zaehol Fatah; Filsa Salsabila (Jurnal Padamu Negeri, 2026)
Advances in technology digital have made web browsers an essential tool for learning, searching for information, and communicating. Google Chrome is often chosen by students because it is easy to use, rich in features, and compatible with online educational services. However, how users manage features such as tabs, extensions, and bookmarks varies. This research seeks to examine how seventh-grade students at SMPN 1 Banyuputih Situbondo use tabs, extensions, and bookmarks in Google Chrome, and the factors that influence their effective use of these features.   A survey method with a descriptive quantitative approach was employed in this study. The material presented was appropriate for seventh-grade students at SMPN 1 Banyuputih Situbondo who regularly use Google Chrome for learning and daily digital activities.   The results of this study suggest that most students have used the tab feature to access multiple information sources simultaneously. However, the use of bookmarks and extensions remains minimal. This low usage is attributed to a lack of understanding of their benefits, functions, and how to manage them. Based on this research, improving digital literacy related to browser administration can enhance the efficiency of information searches, learning productivity, and support more structured management of digital learning resources.